Pengaruh Kompensasi dan Lingkungan Kerja terhadap Kinerja Pegawai Badan Narkotika Nasional Provinsi Sumatera Selatan - Yuli Ismawati; Wiwin Agustian (Economics and Digital Business Review, 2022)
Compensation is an important factor in encouraging and motivating individuals or groups. The higher the compensation, the more motivated employees are to do a better job. The work environment is less important for employees who carry out activities within the company. The work environment provides comfort and tranquility for all company employees. The purpose of the study was to determine the effect of compensation and work environment on employee performance. This type of research is quantitative research. The sample size for this survey was 86 respondents. Data analysis techniques include descriptive analysis, classical hypothesis testing i.e. data normality test, multicollinearity test, heteroscedasticity test, hypothesis test, joint significance test (F-statistic test), partial test (t-test), and multiple linear regression analysis tests were used. The results showed that compensation affected employee performance with a p-value of 0.037 and work environment affected employee performance with a p-value of 0.005. Taken together, compensation and work environment influence employee performance, with a p-value of 0.002.